Design of recyclable, fast-responsive and high temperature shape memory semi-aromatic polyamide. (22nd February 2021) - Yan, Guang-ming; Wang, Han; Li, Dong-sheng; Lu, Hao-ran; Liu, Sui-lin; Yang, Jie; Zhang, Gang
Abstract: Development of high temperature shape memory polymers with fast response time and recyclable performance is highly desired. In this study, a new semi-aromatic tri-amine (TRIA) containing thioether unit is prepared through the reaction of trifluoro-monomer and p-mercaptoaniline (p-MA). It is conducted to polymerize with 4, 4′-thiodibenzoyl chloride (TDC) and different ratios of diamine (both of them contained flexible thioether group) to supply a series of slightly crosslinking semi-aromatic polyamide. It is found that the resultant polymers had excellent thermal properties (Tg, 237.9–245.8 °C, Td, 430.9–436.5 °C) and mechanical properties (tensile strength, 74–100 MPa). Because of the introduction of the large amount of flexible thioether group, the resultant polyamides can be dissolved in some aprotic solvents, and can be processed with solution method to fabricate a series of fast-responsive shape memory film (SMF) with a responsive time of 6–8 s, recovery rate of 98–99.5% after 20 cycles. What's more, the oxidized film can even lift a weight equal to about 2–3 times (vertical direction) and 5–8 times (horizontal direction) of its own weight. Interestingly, unlike other shape memory polymers, these SMF after multiple processes (after bending-recovery cycle at high temperature) can still be processed repeatedly with a solution route, which supplies a novel and recyclable candidate for excellent performance SMP. It is expected to be used in solar cell wingspan actuator to light the satellite weight. Graphical abstract: Image 1 Highlights: The resultant semi-aromatic polyamides were found to have good heat-resistant, fast shape-memory and recyclable properties. The shape memory time of SMP-(2.5–12.5) can reach 8–10 s. SMP-(2.5–12.5) can be used and recycled easily with solution method using NMP as solvent.